A Highly Stretchable, Tough, Self‐Healing, and Thermoprocessable Polyacrylamide–Chitosan Supramolecular Hydrogel. Issue 12 (24th September 2018) - Dutta, Agniva; Maity, Supriya; Das, Rajat K.
Abstract: Polymerization of acrylamide in concentrated aqueous solution in the presence of chitosan and in the absence of covalent cross‐linker leads to the formation of stiff and tough supramolecular polymer hydrogels that are self‐healing, can be stretched up to ≈30 times their original length, and demonstrate rapid self‐recovery, due to the inter‐chain hydrogen bonds between polyacrylamide and chitosan acting as sacrificial bonds to dissipate energy. These gels show thermoplastic behavior and can be molded into different shapes after a heating–cooling cycle, maintaining reasonable mechanical strength. The gels can withstand repeated compressive loading–unloading cycles, exhibiting reliable load‐bearing capacity. Abstract : Polymerization of a concentrated aqueous solution of acrylamide in the presence of chitosan without any chemical cross‐linker produces thermoplastic and remoldable hybrid supramolecular polymeric hydrogels with high strength, stretchability, fracture energy and notch‐insensitivity. The dynamic dissociation and re‐association of the hydrogen bonding cross‐links between the polyacrylamide and chitosan chains endows these gels with self‐healing, rapid self‐recovery and excellent anti‐fatigue properties.